An Efficient Nitroblue Tetrazolium Staining and Bright-Field Microscopy Based Method for Detecting and Quantifying Intracellular Reactive Oxygen Species in Oocytes, Cumulus Cells and Embryos - Javvaji, Pradeep K.; Dhali, Arindam; Francis, Joseph R.; Kolte, Atul P.; Mech, Anjumoni; Roy, Sudhir C.; Mishra, Ashish; Bhatta, Raghavendra (Frontiers in Cell and Developmental Biology, 2020)
Assessment of intracellular reactive oxygen species (ROS) is important for evaluating the developmental ability of cumulus-oocyte complexes (COC) and embryos. Although, fluorescence-based 2′, 7′-dichlorodihydrofluorescein diacetate (DCFH-DA) staining method is used widely for detecting intracellular ROS in COC and embryos, it is associated with several limitations. This study aimed to develop an alternative method for detecting and quantifying intracellular ROS in oocytes, cumulus cells and embryos based on nitroblue tetrazolium (NBT) staining and bright-field microscopy. Nitroblue tetrazolium reacts with ROS and forms formazan precipitate that can be detected as dark purple/blue spots under bright-field microscope. Ovine COC were matured in vitro without (control) or with the supplementation of Interleukin-7 (IL-7; for stimulating intracellular ROS), Tempol (superoxide scavenger) or combination of IL-7 and Tempol. The matured COC were stained with NBT and the formation of intracellular formazan precipitates was assessed. Additionally, the matured COC were stained with DCFH-DA to compare the level of intracellular ROS. Further, ovine embryos (8-cell, morula and degenerating) were generated in vitro and stained with NBT for assessing intracellular ROS. The level of intracellular ROS was expressed as the proportion (%) of the NBT stained area in oocytes, compact cumulus cell masses or embryos. The proportions of NBT stained area in the matured oocytes and cumulus cells was found significantly lesser in the control as compared to the IL-7 (1 and 5 ng/ml) treated groups. A similar trend in the intracellular ROS level was also observed in the matured COC, when assessed based on the DCFH-DA staining. Following the treatment with 100 mM Tempol, negligible NBT stained area in oocytes and cumulus cells was observed. The NBT staining patterns of the oocytes and cumulus cells following the combined treatments with IL-7 (5 ng/ml) and Tempol (10 and 25 mM) were comparable with that of the control. The proportion of the NBT stained area did not differ significantly between the 8-cell embryos and morula, but it was found significantly greater in the degenerating embryos. In conclusion, the developed NBT staining method was found effective for detecting and interpreting the level of intracellular ROS in oocytes, cumulus cells and embryos.